Corporate Social Responsibility (CSR) as a Catalyst for ESG Integration in Marketing Strategies - Monika Handayani; Gusti Putri Nurzhavira (Cita konsultindo, 2024)
Corporate Social Responsibility (CSR) has become integral to modern business strategy. CSR is not only about fulfilling corporate social responsibilities but also about creating long-term value for stakeholders. The research aims to: 1) Identify the role of CSR as a catalyst in integrating ESG in marketing strategy; 2) Analyze the Impact of ESG integration on company performance and marketing strategy; 3) Provide case studies of successful companies implementing CSR as an ESG catalyst in marketing strategies. T The research approach used in this study is qualitative. The research design used is descriptive. This design describes CSR and ESG phenomena in a marketing context. Data was collected through surveys, interviews, and document analysis. Data analysis was carried out using content analysis methods. Content analysis is used to analyze qualitative data from interviews and documents. Integrating CSR and ESG in marketing strategies can provide significant competitive advantages. Integrating CSR into marketing through the lens of ESG can significantly enhance a company's reputation, build consumer trust, and differentiate the brand in a competitive market. Unilever’s successful integration of CSR as an ESG catalyst in marketing demonstrates that sustainability can drive business growth while benefiting society and the environment.